Interaksi Dan Komunikasi Musikal Dalam Garap Sekaten - Bambang Sosodoro (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2018)
AbstractThe traditions that govern the music of gamelan Sekaten are commonly referred to as garap Sekaten. Based on observations of current musical practice, it can be comprehensively stated that garap Sekaten involves musical interaction and communication. This is reflected in the melodic phrases and interactive grammar between particular instruments of this ensemble. The characteristics, unique qualities, and complexities of garap sekaten have also influenced the gamelan ageng. For example, gendhing Bonang are a genre within gamelan ageng repertoire that accentuate the